Therapeutic Options in Hydatid Hepatic Cyst Surgery: A Retrospective Analysis of Three Surgical Approaches - Alin Mihetiu; Dan Bratu; Bogdan Neamtu; Dan Sabau; Alexandra Sandu (Diagnostics, 2024)
Hydatid disease is endemic in certain geographical areas where animal breeding is common, frequently challenging the medical services in these regions. Hydatid cysts most often affect the liver, with damage to other organs accounting for around one-third of the total cases. The alternative to interventional or pharmacological approaches is surgical treatment, available in variants such as laparoscopy, laparoscopy with special instruments for hydatid disease, or open surgery. This article aims to analyze the outcomes of these three types of surgical approaches, considering preoperative indications, operative techniques and efficiency, and immediate and long-term postoperative results. A total of 149 patients from two different surgical units were analyzed over a period of seven years. It was observed that males were more affected by this pathology (53.02%), with the majority of patients coming from rural areas (62.42%). The distribution by surgical procedure type showed that 50.34% were operated on using open surgery, 33.56% by means of a laparoscopic approach with the usual instruments, and 16.11% by means of a laparoscopic approach with special instruments. The laparoscopic procedure with special instruments presented a lower rate of conversion to open surgery compared to the usual laparoscopic approach (p = 0.014). The analysis of the average operative duration revealed statistically significant differences between the three types of surgical techniques (p < 0.05), noting that interventions with specialized instruments had the shortest duration, while open surgery had the longest operative time (72.5 ± 27.23 min vs. 154 ± 52.04 min). In terms of intraoperative complications, they were documented in 8.34% of cases for the group operated on with special instruments, in 12.24% of cases for the standard laparoscopy group, and in 16% of cases for the open surgery group. Maximal cystectomy was the preferred method for resolving these cysts using minimally invasive surgery (p < 0.001), while Lagrot pericystectomy was preferred in the open approach (p < 0.001). The most frequent postoperative complication was biliary fistula (24.16%), encountered in varying percentages across each technique but without significant statistical difference (p > 0.05). Open surgery was associated with a longer length of hospitalization compared to minimally invasive procedures (p < 0.05), a higher number of late postoperative complications (p = 0.002), and a significantly higher number of recurrences (p < 0.001) compared to the other two techniques. The present study highlights the effectiveness of minimally invasive surgery for hydatid cysts as a safe alternative with fewer complications and superior results compared to open surgery. Additionally, it provides a comparative analysis of these surgical approaches (special instruments, standard laparoscopy, and open surgery) to hydatid disease for the first time. Under the circumstances where pharmacological treatment is recommended as a supportive measure before and after procedures, and using medication alone as the primary treatment option shows only modest efficacy, there is a necessity to consider invasive treatment methods. Percutaneous procedures represent the least invasive form of treatment, yielding results comparable to surgery in terms of efficacy. However, their effectiveness is influenced by factors such as the cyst’s stage of development, its location, and the challenges in achieving complete intra-procedural isolation. Laparoscopy, particularly when using specialized instruments tailored to the tactical and technical demands of managing hydatid disease, serves to address the limitations of percutaneous methods. Open surgery’s role is increasingly restricted, primarily serving as a fallback option in laparoscopic procedures or in cases complicated by hydatid disease. In conclusion, despite the rising popularity of percutaneous methods, surgery remains a viable therapeutic option for treating hydatid disease. Minimally invasive surgical interventions are increasingly versatile and yield comparable outcomes, further solidifying the role of surgery in its management.